Sleep Disorders in Leucine-Rich Glioma-Inactivated Protein 1 and Contactin Protein-Like 2 Antibody-Associated Diseases - Lin, Nan; Hao, Honglin; Guan, Hongzhi; Sun, Heyang; Liu, Qing; Lu, Qiang; Jin, Liri; Ren, Haitao; Huang, Yan (Frontiers in Neurology, 2020)
Objective: Sleep disorders are common in voltage-gated potassium channel complex antibody (VGKC-Ab) diseases. The aim was to investigate the sleep disturbances and polysomnography (PSG) characteristics in patients with VGKC-Ab-associated diseases. Methods: Twenty-seven patients with leucine-rich glioma-inactivated protein 1 antibody (LGI1-Ab) encephalitis, seven patients with contactin protein-like 2 antibody (Caspr2-Ab)-associated diseases, and 14 healthy controls with at least one PSG or actigraphy recording were recruited at Peking Union Medical College Hospital from January 2014 to July 2019. Results: Sleep disorders including insomnia, hypersomnia, rapid eye movement (REM) sleep behavior disorder (RBD), periodic limb movements in sleep (PLMS), agrypnia excitata, and obstructive sleep apnea syndrome were observed. Twenty-one PSG recordings from patients with LGI1-Ab encephalitis demonstrated a decrease in total sleep time (TST) (median 365.5, range 184.5–495.5 min), sleep efficiency (70.0%, 47–92%), N3 sleep (9.7%, 0–32.9%), and REM sleep (9.9%, 0.4–27.9%). Of five patients with Caspr2-Ab-associated diseases, TST was found to be 329.5 (167.0–377.5 min), and sleep efficiency was found to be 61.7% (34.6–71.7%). The percentage for N3 and REM sleep was found to be 15.0% (0–34.6%) and 12.7% (0–22.2%), respectively. Both RBD and PLMS were observed more frequently in patients with LGI1-Ab encephalitis. We identified status dissociatus (SD) in five (23.8%) patients with LGI1-Ab encephalitis and two (40%) patients with Caspr2-Ab diseases. The former is more likely to have simple limb movements rather than complex movements, which mimic the contents of their dreams. Continuous insomnia was more common in patients with Caspr2-Ab diseases than patients with LGI1-Ab encephalitis. Patients reported clinical and PSG improvements following immunotherapy. Conclusion: Sleep disorders in patients with VGKC-Ab-associated diseases include decreased TST and poor sleep efficiency. Our studies provide evidence of SD in patients with LGI1-Ab encephalitis.